Experimental characterization and numerical prediction of ductile damage in forming of AA1050-O sheets. (August 2015) - Msolli, S.; Badreddine, H.; Labergere, C.; Martiny, M.; Robin, G.; Jrad, M.; Saanouni, K.; Choquart, F.
Abstract: In this paper, a modeling of the deformation behavior of AA1050-O sheets is presented. The modeling of this kind of material is based on various mechanical tests such as tensile, hydraulic bulge, Marciniak and Nakazima deep drawing, as well as cup drawing tests. These tests are performed on planar sheets of 0.5 mm thickness. The experimental database obtained from planar specimens is used to identify and validate the material parameters of a large strains elastoplastic model based on Hill׳s anisotropic plasticity criteria and coupled with damage. The identified elastoplastic model is then, implemented as a user subroutine – VUMAT- into the finite elements code ABAQUS, and validated by numerical simulations of the deep drawing tests. The Forming Limit Curves (FLC) are also determined numerically and compared to the experimental data. Highlights: We model the mechanical behavior of AA1050 under uniaxial and forming tests. An identification procedure is provided which is based on the performed tests. A deformation-damage model is used for failure and FLC predictions of AA1050-O. A critical damage parameter is calibrated for the determination of FLC.